1981
DOI: 10.1002/hlca.19810640827
|View full text |Cite
|
Sign up to set email alerts
|

Synthese von (−)‐(5R,6S)‐5,6‐Epoxy‐5,6‐dihydro‐β‐ionon

Abstract: Synthesis of (-)-(5R,6S)-5,6-epoxy-5,6-dihydro-/%ionone Summary Optically active 5,6-epoxy-5,6-dihydro-@-ionones have been prepared for the first time and their absolute configurations were determined by correlation with (-)-(9-a-ionone. Acid catalyzed hydrolysis of the epoxide proceeds with retention of the configuration at C(6) and with inversion at C(5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
0
10
1
Order By: Relevance
“…9) Screening among fungi revealed that Aspergillus awamori lAM 2299 was the most potent microorganism. When fJ-ionone (5) 7 ,9,10) The difference between the results of Mikami's group and ours may be attributable to the different microorganism, although the details are not clear.…”
Section: -5)contrasting
confidence: 42%
See 1 more Smart Citation
“…9) Screening among fungi revealed that Aspergillus awamori lAM 2299 was the most potent microorganism. When fJ-ionone (5) 7 ,9,10) The difference between the results of Mikami's group and ours may be attributable to the different microorganism, although the details are not clear.…”
Section: -5)contrasting
confidence: 42%
“…The first attempt was a direct approach, i.e., the microbial hydroxylation ofp-ionone (5) by fungi. 9) Screening among fungi revealed that Aspergillus awamori lAM 2299 was the most potent microorganism.…”
Section: -5)mentioning
confidence: 99%
“…Epoxy-β-ionone 5 has been found in nature in tomatoes, [43] carrots, [44] raspberries, [45] black tea, [46] and tobacco, [47] and has been prepared in enantiomerically enriched forms both by resolution [40,48,49] and by enantioselective synthesis. [50] a) Resolution of the Racemate Optically active 5,6-epoxy-5,6-dihydro-β-ionones were prepared for the first time in 1981, by Eugster et al, [48] and their absolute configurations were determined from the starting materials, the optically active α-ionones (1).…”
Section: 6-epoxy-56-dihydro-β-iononementioning
confidence: 99%
“…[50] a) Resolution of the Racemate Optically active 5,6-epoxy-5,6-dihydro-β-ionones were prepared for the first time in 1981, by Eugster et al, [48] and their absolute configurations were determined from the starting materials, the optically active α-ionones (1). The (Ϫ)-and (ϩ)-4-hydroxy-β-ionones 35 were prepared [37] from the corresponding cis-epoxy-α-ionones, and submitted to Sharpless oxidation to provide cis-hydroxyoxirane 39 In 1990, a solid-state kinetic resolution of epoxy-β-ionone was reported by Toda et al [49] A 1:1 inclusion complex between racemic β-ionone and the optically active host (Ϫ)-trans-2,3-bis(hydroxydiphenylmethyl)-1,4-dioxaspiro [5.4]decane (42) was treated with 3-chloroperbenzoic acid.…”
Section: 6-epoxy-56-dihydro-β-iononementioning
confidence: 99%
“…(-)-1. Thermolysis of (-)-l [34] ("ID = -92" (c = 1.0, CHCI,); 27 mg, 0.13 mmol) at 455' led to a mixture (25 mg) of (-)-1 (88 Yo) and 13 (10%); the mixture was chromatographed (12 g SO,, AcOEt/hexane 1:4) to yield (-)-1 (17 mg; [aID = -92" (c = 1.0, CHCI,)). …”
Section: (E)-4-(i'2'-epoxy-2'6'6'-trimethvlcyclohexyl)-3-huten-2-onementioning
confidence: 99%